Judicial Rhapsodies - Coulson, Doug (Amherst College Press, 2023)
All judges legitimize their decisions in writing, but US Supreme Court justices depend on public acceptance to a unique degree. Previous studies of judicial opinions have explored rhetorical strategies that produce legitimacy, but none have examined the laudatory, even operatic, forms of writing Supreme Court justices have used to justify fundamental rights decisions. Doug Coulson demonstrates that such “judicial rhapsodies” are not an aberration but a central feature of judicial discourse.